Kajian Penggunaan Dewan Sengketa pada Proyek Konstruksi di Indonesia (Studi Kasus: Proyek MRT Jakarta Fase 2A) - Nugroho, Rafi; Iris Mahani (Universitas Nusa Putra, 2025)
The interaction between construction industry and projects can lead to inevitable construction disputes that need immediate resolution. Dispute boards can be an alternative for preventing and resolving construction disputes. This research aims to identify strengths, weaknesses, opportunities, threats, and strategies for using dispute boards in Indonesian construction projects based on case study of MRT Jakarta Phase 2A Project. The research method is qualitative descriptive using Internal Factors Analysis Strategic (IFAS) to identify strengths and weaknesses and External Factors Analysis Strategic (EFAS) to identify opportunities and challenges then conducted to develop strategies for using a dispute board using SWOT Analysis. The findings indicate that standing dispute boards in construction projects can prevent escalation and improve the effectiveness of dispute resolution. However, the success of dispute boards depends on the trust from the involved parties and high costs needed. The use of dispute boards in Indonesia can fulfill the needs for dispute resolution during projects though the lack of awareness about the importance of dispute prevention and the limited number of qualified board members hinders widespread adoption. Strategies for using dispute boards in Indonesian construction projects include implementing regulations and granting the right to use dispute boards for all parties.